Clonidine and morphine increase [3H]-noradrenaline overflow in mouse vas deferens. - Forsyth, K. M. (1988)
1. Field stimulation of mouse isolated vas deferens produced a biphasic contraction that consisted of an initial brief non-adrenergic, non-cholinergic (NANC) twitch, followed by a more prolonged noradrenergic component. 2. Field stimulation of vasa, previously loaded with [3H]-noradrenaline ([3H]-NA), increased the amount of radioactivity in the Krebs bathing solution; 77% of this radioactivity was derived from [3H]-NA. 3. Tetrodotoxin (3 x 10(-6) M) abolished the biphasic motor response to field stimulation and the accompanying increased overflow of [3H]-NA. 4. Morphine (10(-7)-10(-5) M) inhibited the initial NANC component but potentiated the secondary noradrenergic component of the motor response to field stimulation. Morphine also increased the field stimulation-induced overflow of radioactivity. Naloxone (10(-6) M) antagonized the effects of morphine on the motor response and also on the overflow of radioactivity. 5. Clonidine (10(-9)-10(-7) M) inhibited the initial NANC component but potentiated the secondary noradrenergic component of the motor response to field stimulation. Clonidine also increased the field stimulation-induced overflow of radioactivity. 6. The ability of morphine (10(-7) M) and of clonidine (10(-9) M) to potentiate the field stimulation-induced overflow of radioactivity persisted in the presence of a combination of tranylcypromine (10(-5) M), desmethylimipramine (10(-5) M) and 17-beta-oestradiol (10(-5) M). 7. The inhibition of the initial NANC component of the motor response to field stimulation produced by morphine and clonidine may be related to the ability of these drugs to potentiate both the secondary noradrenergic component and the overflow of radioactivity, if the NANC transmitter is involved in regulating NA release.